It ain't necessarily so : the dream of the human genome and other illusions - Lewontin, Richard C., 1929- (New York : New York Review of Books, 2000)
"In these essays from the New York Review of Books, several of which are here updated with new epilogues, Richard Lewontin demystifies some of the most controversial issues in the life sciences today. On topics ranging from Darwin to Dolly the sheep, including biological determinism, heredity and natural selection, evolutionary psychology and altruism, sex surveys, cloning and the Human Genome Project, he offers both sharp criticisms of the overweening pride of scientists, especially those who have mistaken their social prejudices for scientific facts, and lucid expositions of the exact state of scientific knowledge. In each case, he casts an eye on the temptation to overstate the power of biology to explain everything we want to know about ourselves."--BOOK JACKET.
Ch. 1. The Inferiority Complex -- Ch. 2. Darwin's Revolution -- Ch. 3. Darwin, Mendel, and the Mind -- Ch. 4. The Science of Metamorphoses -- Ch. 5. The Dream of the Human Genome -- Ch. 6. Women Versus the Biologists -- Ch. 7. Sex, Lies, and Social Science -- Ch. 8. The Confusion over Cloning -- Ch. 9. Survival of the Nicest?
Includes bibliographical references.
Keywords: Nature and nurture; Human genetics; Genetics; Human biology; Biology